Locomotor respiratory coupling strategies during walking - O'Halloran, J.; Hamill, J.; McDermott, W.; Remelius, J.; van Emmerik, R. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Recent research within human biomechanics has focused on variability in coordinative behavior. Using this approach, insight into the adaptive properties of the locomotor and respiratory systems was achieved by studying the coordinative properties that emerged in response to manipulating the constraints on these systems. Stride frequency (SF) was altered above and below preferred while participants walked at their preferred walking speed. Return map techniques allowed frequency and phase coupling strength and stability to be evaluated. As SF was decreased the dominant coupling was 2:1; when SF was increased the dominant coupling was 3:1. Strength of frequency coupling did not change with altered SF. The variability in locomotor respiratory coupling observed, particularly in phase coupling, strongly point to the necessity of variability, and not entrainment, in these rhythms.